International Human Rights Regime as an Instrument for Advancing National Interests: : The US and Others in the 21st century - Eze, Malachy Chukwuemeka (Society & Sustainability, 2020)
This paper examines the relationship between international human rights regimes and the pursuit of United Sates national interests in the 21st century. Archival research or literature survey, content analysis, and the realist theory of international human rights were adopted for the inquiry. The core objectives of the paper were to assess US human rights posture; find out if US international defence of human rights and interventions is without bias; and to determine if there is a positive relationship between US pursuit of national interest and US human rights policy. The results of analysis show that US has both internal and external poor human rights posture; and there is lack of neutrality in US international human rights campaign. The results further reveal that there are different supranational principles of human rights and institutions; and although the US refused to ratify key international human rights regimes, they have being used consistently to advance US national interests. It is therefore concluded that international human rights regimes are weakened by conflict of value systems and Great powers politics.